2019
DOI: 10.1038/s41467-019-13210-5
|View full text |Cite
|
Sign up to set email alerts
|

Rpd3L and Hda1 histone deacetylases facilitate repair of broken forks by promoting sister chromatid cohesion

Abstract: Genome stability involves accurate replication and DNA repair. Broken replication forks, such as those encountering a nick, lead to double strand breaks (DSBs), which are preferentially repaired by sister-chromatid recombination (SCR). To decipher the role of chromatin in eukaryotic DSB repair, here we analyze a collection of yeast chromatin-modifying mutants using a previously developed system for the molecular analysis of repair of replication-born DSBs by SCR based on a mini-HO site. We confirm the candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 74 publications
2
38
0
Order By: Relevance
“…Recombination frequencies were calculated by transforming the indicated yeast strains with the pTINV-FRT plasmid containing an leu2 inverted-repeats recombination system 66 . Recombination tests were performed in mid-log phase cultures after growth at 30°C in liquid SC media with 2 % raffinose and 5 mg/ml doxycycline but lacking uracil.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombination frequencies were calculated by transforming the indicated yeast strains with the pTINV-FRT plasmid containing an leu2 inverted-repeats recombination system 66 . Recombination tests were performed in mid-log phase cultures after growth at 30°C in liquid SC media with 2 % raffinose and 5 mg/ml doxycycline but lacking uracil.…”
Section: Methodsmentioning
confidence: 99%
“…Recombination frequencies were calculated by transforming the indicated yeast strains with the pTINV-FRT plasmid containing an leu2 inverted-repeats recombination system 66 .…”
Section: Analyses Of Rad52 Foci and Genetic Analyses Of Recombinationmentioning
confidence: 99%
“…Using a powerful-engineered system in which nicks are induced by the action of the yeast endonuclease HO into an incomplete target sequence placed in a reporter gene, we have shown that mutants of the yeast Rpd3 and Hda1 HDACs strongly impair SCR. 2 Furthermore, we have improved the system by substituting the endonuclease HO by a modified version of the flipase (FLP) so that nicks can be specifically targeted to a flipase recognition site located on either DNA strand. This has enabled us to see that the kinetics of repair of broken forks with the sister chromatid is similar regardless of whether the nick was induced in the leading or lagging strand.…”
mentioning
confidence: 99%
“…Interestingly, HDACs affect SCR because they are required for the proper loading of cohesins. 2 Cohesin is a conserved multi-subunit protein complex that hold the sister chromatids together thus enabling proper SCR, as shown in yeast and human cells. 4,5 Cohesion is established during replication and lasts until the onset of mitosis to enable the separation of the sister chromatids, but additional cohesins have been shown to load upon DNA damage independently of replication.…”
mentioning
confidence: 99%
See 1 more Smart Citation